An unusual presentation of vaginal leiomyoma - Rahul R. Patil; Nikita R. Vijay; Sulbha Joshi (Wolters Kluwer Medknow Publications, 2019)
Leiomyomas are classified as benign mesenchymal neoplasms and consist of smooth muscle cells with variable amounts of fibrous stroma. The tumors occur most frequently in the uterus, affecting 20%-30% of women of reproductive age, but vaginal leiomyomas are rare with only around 300 cases reported since the first case was described in 1733. These tumors are thought to arise from Müllerian smooth muscle cells in the subepithelium of the vagina. Here, we present a case of vaginal leiomyoma who presented as left vaginal wall mass.